Darwin Endures, Despite Disparagement. (March 2018) - Van Den Berg, Hugo A.
Evolution lies at the heart of the life sciences, and Charles Darwin is a towering historical figure within evolutionary science. One testimony to his lasting influence is that declaring Darwin to have been wrong all along remains a provocative way to command attention. The present paper discusses various strands of 'Darwin was wrong' partisans and their divergent views and motives: some are looking to Darwin to justify or condemn the political ideologies that they support or reject; others are concerned with the corrupting influence that the bleak cosmic outlook of evolution is deemed to exert on the moral or religious rectitude of impressionable minds, or regard Darwinism as a direct assault on religion; philosophers question the very coherence of the entire enterprise; and certain biologists aspire to go down in history as even greater than Darwin. It is sobering to reflect that this diverse group is united only by their poor grasp of Darwin's theory of natural selection.